Global biodiversity-related conventions on facilitating biodiversity conservation in Vietnam - Tung, Do Quang; Bravo, Felipe; Sierra-de-Grado, Rosario; Sam, Hoang Van (Forestry Faculty, Universitas Hasanuddin, 2022)
Global biodiversity-related conventions have positively influenced nature conservation in Vietnam. Adherence to international policies and strategies is one of the critical motivations for reducing biodiversity loss. As highlighted in Aichi Target 11, protected areas are central for this effort and Vietnam is not an exception. In this study we reflect on and suggest how this Target can be most effectively pursued in Vietnam. Of which, besides remaining the status of special-use forests, uplifting protection forests, especially focusing on forest areas which are in rich biodiversity condition, to special-use forests category should be a priority.